Antiplatelet therapy for patients with COVID-19: Systematic review and meta-analysis of observational studies and randomized controlled trials - Zong, Xiaolong; Wang, Xiao; Liu, Yaru; Li, Zhenyu; Wang, Weiding; Wei, Dianjun; Chen, Zhuqing (Frontiers in Medicine, 2022)
Background Hyperinflammation and coagulopathy are hallmarks of COVID-19 and synergistically contribute to illness progression. Antiplatelet agents have been proposed as candidate drugs for COVID-19 treatment on the basis of their antithrombotic and anti-inflammatory properties. A systematic review and meta-analysis that included early observational studies and recent randomized controlled trials (RCTs) was performed to summarize and compare evidence on this issue. Methods PubMed, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched to identify studies published up to Nov 7, 2021, and the results of registered clinical trials were followed up to Mar 30, 2022. We included RCTs and observational studies assessing the effect of antiplatelet therapy in adult patients with COVID-19. Data on baseline patient characteristics, interventions, controls, and outcomes were extracted by two independent reviewers. The primary outcome was mortality. Data were pooled using a random-effects model. Results Twenty-seven studies were included, of which 23 observational studies were pooled in a meta-analysis, and the remaining four RCTs (ACTIV-4B, RECOVERY, ACTIV-4a, and REMAP-CAP) were narratively synthesized. Based on 23 observational studies of 87,824 COVID-19 patients, antiplatelet treatment favors a lower risk of mortality [odds ratio (OR) 0.72, 95% confidence interval (CI) 0.61–0.85; I2 = 87.0%, P < 0.01]. The narrative synthesis of RCTs showed conflicting evidence, which did not support adding antiplatelet therapy to the standard care, regardless of the baseline illness severity and concomitant anticoagulation intensity. Conclusion While the rationale for using antiplatelet treatment in COVID-19 patients is compelling and was supported by the combined result of early observational studies, evidence from RCTs did not confirm this approach. Several factors that could explain this inconsistency were highlighted alongside perspectives on future research directions.